New Media: Instagram @sumbar_rancak as a Means of Promoting Tourism in West Sumatra - Engga Probi Endri; Kurniawan Prasetyo (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2021)
The development of social media today has a big impact, one of which has an impact in the field of promotion. Industry players including influencers and content creators use Instagram social media as a means of promotion, one of which is Instagram @sumbar_rancak social media as a means of promoting tourism in Sumatera Barat. Based on the above background, the focus of the problem in this study is how to use social media instagram @sumbar_rancak as a means of tourism promotion in Sumatera Barat. The purpose of this study was to determine the use of social media Instagram @sumbar_rancak as a means of promoting tourism in Sumatera Barat. This study uses the concept of new media-based tourism promotion, namely social media Instagram. This research will use a qualitative approach using the case study method. From the research results, the use of Instagram @sumbar_rancak social media as a means of tourism promotion in Sumatera Barat is to use several Instagram features such as; photo title or caption, hashtags, comments, mentions. And based on the results of observations and interviews with Instagram informants, @sumbar_rancak is very effective in promoting tourism in West Sumatra. This is evidenced by the statements of visitors through the captions they upload on privately owned social media.